Calcium and Boron Effect on Production and Quality of Autumn Potato Crop Under Chilling Temperature. Issue 4 (21st February 2021) - Ilyas, Mohammad; Ayub, Gohar; Imran,; Ali Awan, Azmat; Ahmad, Manzoor
ABSTRACT: Field experiments were conducted to study the effect of calcium (Ca), Boron (B) and their combination, i.e., 0, (0.03%Ca), (0.06%Ca), (0.02%B), (0.04%B), (0.03%Ca) + (0.02%B), (0.03%Ca) + (0.04%B), (0.06%Ca) + (0.02%B) and (0.06%Ca) + (0.04% B) on production and quality of autumn potato crop. Results revealed that different sowing dates, Ca, B treatments and their interaction significantly affected yield and quality parameters of potato crop. The application of Ca alone @ 0.06% significantly increased the large tubers plant −1 (2.0), total yield (18.6 t ha −1 ), survival (78%), dry matter content (18.3%) and starch content (14.6%) as compared to control treatment. Boron @ 0.04% also significantly enhanced large tubers plant −1 (2.1), total yield (18.7 t ha −1 ), survival (75%), dry matter content (18.2%) and starch content (14.9%) than control treatment. Foliar application of (0.06% Ca) + (0.02% B) resulted in the maximum number of large tubers plant −1 (2.5), total yield (20.5 t ha −1 ), dry matter content (19.5%) and starch content (16.2%) as compared to other treatment combination. Plant survival was maximum at (0.06% Ca) + (0.04% B). Increasing Ca, B concentration decreased in number of small size tubers plant −1 . Early sown potato plants with the combined application of 0.06% Ca + 0.02% B resulted in maximum yield and quality characteristics as compared to the rest. So it is concluded that early planting in the first week of October with the combined application of 0.06% Ca + 0.02% B resulted in maximum yield and quality of potato.